(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
: This paper aims to analyze the inadequate use of the extraordinary resource to address the factual question concerning the title of property of the traditional occupation area of ​​Xavantes, in the state of Mato Grosso. Thus, the Federal Constitution of 1988 and the Code of Civil Procedure will be the contribution of the research. The constitutional text substantiates the possession of traditional territory, and provides normative prescriptions essential to the referred appeal, and procedural rules concern the nature of the extraordinary appeal. To make the research possible, the hypothetical deductive method is employed based on the following question: Why is the use of the extraordinary resource considered inappropriate to question the factual matter? Thus, the specific objective is to demonstrate the inappropriate use of the extraordinary resource to question the property title of the traditional Xavante territory. And the general objective is the analysis of the traditional possession given by the constitutional text, and the nature of the extraordinary appeal. As methodological procedures we used the bibliographic and qualitative research.